The Complexity of Ethnic Identity Among Jewish American Emerging Adults. Issue 3 (2nd July 2016) - Weisskirch, Robert S.; Kim, Su Yeong; Schwartz, Seth J.; Whitbourne, Susan Krauss
ABSTRACT: Jewish Americans may grapple with issues of ethnic identity differently than the larger White American group. Drawn from a large multisite sample ( N  = 8, 501), 280 Jewish American (207 female, 73 male) emerging adults were compared with White American and ethnic minority samples on ethnic and U.S. identity. Jewish Americans rated themselves as significantly higher on measures of ethnic and U.S. identity compared with White Americans but not as highly as ethnic minorities. Ethnic identity search, affirmation, and resolution also predicted higher self-esteem for Jewish Americans, similar to the pattern for other ethnic groups. In addition, ethnic identity search and affirmation moderated the link between perceived discrimination and depressive symptoms among Jewish Americans.